International Students in American Colleges and Universities: A History - LeBeau, Ling Gao (Journal of International Students, 2012)
International Students in American Colleges and Universities: A History provides a comprehensive historical overview of international student exchange in the U.S. The purpose of this book is to trace the history of international students in institutions of American higher education by enumerating why and how international students have studied in the U.S. since the 18th century. It also provides an overview of international students’ impact on American higher education and society. International educators will not only obtain historical knowledge of international students but also become enlightened about the field of internationalization.